Studying Affixation Errors Found in Mini Drama Scripts Composed by The Students of Universitas Trunojoyo Madura - Anidya Gita Ismaningsih; Afiifah Al Rosyiidah (Journal of Social, Culture, and Language, 2025)
This study aims to explain the types of affixation errors and the factors that cause these errors in mini drama scripts written by the fourth-semester students of the English Study Program at Universitas Trunojoyo Madura, specifically from the A and B classes of 2021. This study is a descriptive qualitative research and uses a document analysis method to collect the data. There are 10 mini-drama scripts used as the data sources, and the data are words or phrases containing affixation errors. The technique of analyzing the data include data condensation, data display, and drawing and verifying conclusions. The identified errors are described based on the surface taxonomy and the types of affixations. The findings show that there are 35 total of affixation errors found in 10 mini drama scripts, which include only two types of errors based on the surface taxonomy: 32 omission errors and 3 addition errors. These errors involve the inflectional suffixes, such as -s (third-person singular), -ing (present participle), -d/-ed (past tense), -ed/-n (past participle), and -s (plural marker), and also derivational suffixes -ly and -ed. A total of 28 errors are caused by intralingual transfer, while the other 7 errors are caused by interlingual transfer. In summary, students’ lack of understanding of English affixation, and the differences in its usage between English and Indonesian, influenced the production of these errors in their writing. Keywords: error analysis, affixation errors, mini-drama scripts, interlingual transfer, intralingual transfer